Comparison of the tube test and column agglutination techniques for anti‐A/‐B antibody titration in healthy individuals. Issue 8 (24th September 2018) - Matsuura, Hideaki; Akatsuka, Yoshiki; Matsuno, Takahiro; Sugiura, Yukari; Arakawa, Shoko; Oikawa, Shota; Yoshida, Jumpei; Kosugi, Mitsuaki; Emi, Nobuhiko
Abstract : Background and Objectives: Determination of the anti‐A/‐B titre pre‐ and post‐transplantation is beneficial for treatment selection. Currently, the recommended method for antibody titration is the tube test (TT) assay. Dithiothreitol (DTT) is used for IgM antibody inactivation. Recently, a fully automated antibody titration assay using the column agglutination technique (CAT) was developed (auto‐CAT). Our aim was to compare the auto‐CAT and TT techniques for ABO antibody titration, to evaluate the effectiveness of DTT‐treated plasma for use with auto‐CAT and to define the cut‐off value for antibody titration by auto‐CAT. Materials and Methods: We enrolled 30 healthy individuals, including 10 each for blood types A, B and O. We performed antibody titre measurement using the TT technique and auto‐CAT simultaneously. Auto‐CAT uses the bead column agglutination technology. Results: With the auto‐CAT cut‐off value set to weak (w)+ with DTT treatment plasma, the concordance rate was 45%, and the weighted kappa value between TT and auto‐CAT results was 0·994 in all subjects. Furthermore, there was a significant positive correlation between the anti‐A/‐B titre results obtained using the TT technique and auto‐CAT in all blood types. Moreover, a positive bias (falsely elevated end‐points due to agglomeration of A/B cells) was not observed in auto‐CAT testing using DTT‐treated plasma. Conclusion: Our results show that 1+ agglutination using the TT technique is equivalent to w+ agglutination obtained using auto‐CAT. We recommend that DTT may be used with auto‐CAT to measure antibody titres. Thus, we suggest that auto‐CAT is useful for antibody titration in routine examination.